1991
DOI: 10.1128/jvi.65.5.2393-2401.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and sequence analyses of antibody-selected antigenic variants of herpes simplex virus show a conformationally complex epitope on glycoprotein H

Abstract: Thirteen antigenic variants of herpes simplex virus which were resistant to neutralization by monoclonal antibody 52S or LP11 were isolated and characterized. The antibodies in the absence of complement potently neutralize infectivity of wild-type virus as well as inhibit the transfer of virus from infected to uninfected cells ("plaque inhibition") and decrease virus-induced cell fusion by syncytial strains. The first variant isolated arose in vivo. Of 66 type 1 isolates analyzed from typing studies of 100 cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 54 publications
(62 reference statements)
4
23
0
Order By: Relevance
“…Antibodies against several gH-homologous herpesviral glycoproteins have been found to possess neutralizing activity (7,12,13,15,35,36). The anti-gH(PrV) peptide sera described in this report did not exhibit significant neutralizing activity either with or without addition of complement (data not shown).…”
mentioning
confidence: 59%
“…Antibodies against several gH-homologous herpesviral glycoproteins have been found to possess neutralizing activity (7,12,13,15,35,36). The anti-gH(PrV) peptide sera described in this report did not exhibit significant neutralizing activity either with or without addition of complement (data not shown).…”
mentioning
confidence: 59%
“…As a second method, we used ELISA to show that the purified complex reacts with MAbs LP11, 53S, and 37S (49). Previous studies had shown that MAbs 52S, 53S, and LP11 recognize different conformation-dependent epitopes (15,18,23,46) and 37S recognizes a linear epitope (46). Thus, these two experiments indicate that gHt in the complex is antigenically correct.…”
Section: Resultsmentioning
confidence: 99%
“…Several criteria suggest that the truncated soluble complex that we are studying reflects the actual structure of the complex in the virion envelope. First, the gHt-gL complex was antigenically intact, as judged by its capacity to bind to MAbs 52S and 53S, which recognize gH conformation (49), as well as to the "gold standard" MAb LP11 (4), which recognizes conformation of the gH-gL complex (23). The baculovirus-derived truncated form of HSV-1 gH-gL (59) also bound to these antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of gH1 have been found in members of all three subfamilies of herpesviruses (Alpha-, Beta-, and Gammaherpesvirinae) (3,18,21,23,28,29,36). gH of HSV-1 plays a role in the process of the cell-to-cell spread of virions and is required for the penetration of virions into cells (4,9,11,12,17,20). HSV-1 gH produced in mammalian expression systems is retained in the cell, most likely in the endoplasmic reticulum or cis-Golgi, and contains oligosaccharide chains that are not fully processed (7,19).…”
mentioning
confidence: 99%